If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25 + 5x = -80 + -2x Solving 25 + 5x = -80 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 25 + 5x + 2x = -80 + -2x + 2x Combine like terms: 5x + 2x = 7x 25 + 7x = -80 + -2x + 2x Combine like terms: -2x + 2x = 0 25 + 7x = -80 + 0 25 + 7x = -80 Add '-25' to each side of the equation. 25 + -25 + 7x = -80 + -25 Combine like terms: 25 + -25 = 0 0 + 7x = -80 + -25 7x = -80 + -25 Combine like terms: -80 + -25 = -105 7x = -105 Divide each side by '7'. x = -15 Simplifying x = -15
| -4.9t^2+355t+87=0 | | 22(2y+1)= | | 2x+2(2x+8)=772 | | 20-2z=26 | | 3z-4z=2 | | 4x+9.8=5.8x-5.86 | | 2(x-5)=3(x-4) | | 2-7.2m=14-4.8m | | 8(4u+-1)-12u=11(2u+-6) | | x(2x-5)(x+6)=0 | | -3G-5=6G+40 | | x+2x+8=772 | | y=2(-1)2+3 | | 8y-20=-6y+50 | | -4(2b+3)+(9b-5)=0 | | 3(x+10)-0.07(x-40)=8.1 | | -5k+5=25 | | 3x-8=-32 | | 7v^2+4=-29v | | 1x-5x^2=0 | | -9+-8= | | 1.4q-3.1-4.7q=4.3q-4.7 | | 5(x+9)+4=-6(x-9)-7 | | b^2-4b=02 | | -8=3t+6 | | 14x-4(9x-40)=355 | | m^2=45 | | 5p-24=-28+3p | | y=-0.8x+6 | | x-2+2=1 | | m^2+20m-85=-4 | | 20-x=19-2x |